THE INFLUENCE OF WORK CULTURE AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE IN SERVICE EMPLOYEES BINJAI CITY PUBLIC WORKS AND SPATIAL PLANNING - Eli Sumitro Sebayang; Kiki Farida Ferine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to analyze the influence of work culture and compensation on employee performance with organizational commitment as an intervening variable. The research location is in the Office of Public Works and Spatial Planning in Binjai City. The population of this study is 79 employees and the sample used is the entire population of 79 employees (saturated sample). The data collection used was a questionnaire. The research model used was path analysis and the measurement tool used Smart PLS version 3.3.3. The results of this study are that work culture has a positive and significant effect on employee performance. Work Culture has a positive and significant effect on Organizational Commitment. Organizational Commitment has a positive and significant effect on Employee Performance. Compensation has no significant positive effect on Employee Performance. Compensation has no significant positive effect on Organizational Commitment. Organizational Culture influences Employee Performance through Organizational Commitment in a positive and insignificant way. Compensation has an effect on Employee Performance through Compensation in a positive and not significant way.